An Enhanced FPGA Based Asynchronous Microprocessor Design Using VIVADO and ISIM - Archana Rani; Naresh Grover (Institute of Advanced Engineering and Science, 2018)
This paper deals with the novel design and implementation of asynchronous microprocessor by using HDL on Vivado tool wherein it has the capability of handling even I-Type, R-Type and Jump instructions with multiplier instruction packet. Moreover, it uses separate memory for instructions and data read-write that can be changed at any time. The complete design has been synthesized and simulated using Vivado. The complete design is targeted on Xilinx Virtex-7 FPGA. This paper more focuses on the use of Vivado Tool for advanced FPGA device. By using Vivado we get enhaced analysis result for better view of properly Route and Placed design.